High-density perovskite thin film, preparation method and application of high-density perovskite thin film in X-ray detection

By coating the precursor vertical liquid of the perovskite material on the electronic transmission layer, combined with vacuum drying and steaming technology, a high -density osteotic membrane is prepared, solving the cracks of the existing perovskite film in the X -ray detector , Defects and integrated issues have realized high -quality and high -performance percotical film.

CN119365036APending Publication Date: 2025-01-24XUZHOU TIKE MEASUREMENT TECHNOLOGY RESEARCH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411390420.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing perovskite films have problems such as many cracks, many grain boundary defects, thin thickness, and rough surface in X-ray direct detectors, making it difficult to integrate with the base circuit, affecting the performance of the detector.

Method used

Using the method of coating the oscope orerite material on the electronic transmission layer, the method of mixing the preliminary liquid of the front -drive body solution of the auxiliary crystal additives and the front -drive body, prepare a high dense perovskin film through the two -step method of vacuum drying and steaming plating to promote the crystallization and the amount of crystals and Surface modification to improve the quality and integration of the film.

Benefits of technology

Realized the preparation of high -quality, thick -controlled high -quality perovskite film, reduced the defects inside the film, improved the charge transmission performance and X -ray response performance, promoted the integration with the conductive substrate, and improved the performance of the detector. And stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365036A_ABST
    Figure CN119365036A_ABST
Patent Text Reader

Abstract

The invention discloses a high-density perovskite thin film, a preparation method and application of the high-density perovskite thin film in X-ray detection. The preparation method of the high-density perovskite thin film comprises the following steps: coating an electron transport layer with a precursor stock solution containing a perovskite material and an auxiliary crystallization additive, and then drying. The perovskite material is selected from one or more of FACs2AgBiBr6, FAMACsPbBr3, CsPbBr3, MAPbBr3, Cs2AgBiBr6 and MAPbI3, and the perovskite material is selected from one or more of FACs2AgBiBr6, FAMACsPbBr3, CsPbBr3 and MAPbI3; the auxiliary crystallization additive is selected from thiourea, biuret, ammonium chloride and the like; the precursor solvent is selected from dimethyl sulfoxide, dimethyl formamide and the like. By adding the auxiliary crystallization additive, homogeneous crystallization of perovskite is promoted, and the prepared film has high compactness, low defect rate, flat surface and controllable thickness, and is suitable for large-area devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of direct X-ray detection of perovskites, and in particular to a high-density perovskite film, a preparation method and application thereof in X-ray detection. Background Art

[0002] X-ray direct detector is an imaging technology that uses semiconductor materials to directly convert X-rays into electrical signals in one step. There is no need to use photodiodes when building devices. The structure is simpler and more efficient, and harmful scattering effects are minimized to achieve higher spatial resolution and sensitivity. Metal halide perovskite is considered to be one of the ideal absorption materials for direct X-ray detection because of its advantages such as large atomic number, high carrier mobility-lifetime product (μ-τ) and large resistivity. However, due to the strong penetration characteristics of X-rays and the need for large-area imaging of detectors, this places great demands on the thickness (greater than 900um) and size (greater than 5×5cm) of the perovskite film. 2 ) has put forward higher requirements. At present, the commonly used methods for preparing perovskite films on a large area mainly include scraping, spraying, vapor deposition, vacuum evaporation and slit coating, but these large-area coating processes involve complex perovskite nucleation and crystallization processes, which lead to problems such as poor uniformity of perovskite film formation, many grain boundaries, cracks, etc., and it is difficult to integrate with the substrate circuit. Therefore, how to develop a large-size, thickness-controlled, high-quality perovskite film based on integrated circuits is the key to promoting the industrialization of X-ray direct detectors. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a high-density perovskite film, a preparation method and its application in X-ray detection. One of the specific technical problems to be solved is to provide a preparation method of a high-density perovskite film, which has a large size and controllable thickness based on an integrated circuit, can induce homogeneous crystallization of perovskite, improve the quality of the perovskite film and improve its surface morphology, and is used to solve the problems of many cracks, many grain boundary defects, thin thickness, rough surface, etc. in the current perovskite X-ray direct detector; the second technical problem to be solved is to provide a high-density perovskite film; the third technical problem to be solved is to provide an application of a high-density perovskite film in the preparation of a perovskite X-ray direct detector.

[0004] In order to achieve the above object, the present invention is implemented by the following steps:

[0005] The invention discloses a method for preparing a high-density perovskite film, comprising the following steps: coating an electron transport layer with a precursor solution and then drying, wherein the precursor solution is a precursor solution whose solute is a perovskite material and an auxiliary crystallization additive and whose solvent is a precursor solvent.

[0006] Preferably, the perovskite material is one or more of FACs2AgBiBr6, FAMACsPbBr3, CsPbBr3, MAPbBr3, Cs2AgBiBr6 and MAPbI3.

[0007] Preferably, the auxiliary crystallization additive is one or more of thiourea, biuret, pyrrole, ammonium chloride, ammonium bromide, ammonium iodide, carbazole, dibenzofuran, imidazoline, butylamine acetate, polyacrylamide, chitosan, cellulose, oleic acid, oleylamine and N,N-diphenylthiourea.

[0008] Preferably, the precursor solvent is one or more of dimethoxyethanol, polyethylene glycol, N-methyl-2-pyrrolidone, N,N-dimethylformamide, chlorobenzene, acetone, dimethyl sulfoxide, dimethylacetamide, chlorobenzene, toluene and chloroform.

[0009] Preferably, the mass ratio of the auxiliary crystallization additive to the perovskite material is (0.001-0.2):1.

[0010] Preferably, the ratio of the auxiliary crystallization additive to the precursor solvent is 0.01 g / ml-0.03 g / ml.

[0011] Preferably, the coating amount of the precursor solution on the electron transport layer is 0.1-1 g / cm2 of the electron transport layer.

[0012] Preferably, the size of the high-density perovskite film is 2×2 cm 2 -30×30cm 2 .

[0013] The invention also discloses a high-density perovskite film, which is prepared by using the above method.

[0014] The present invention also discloses an application of a high-density perovskite film in X-ray detection. Specifically, the high-density perovskite film is used to prepare a perovskite X-ray direct detector.

[0015] Furthermore, the present invention also discloses a method for preparing a perovskite X-ray direct detector, comprising the following steps:

[0016] S1: coating a tin dioxide dispersion on a substrate, drying, and preparing an electron transport layer; the substrate is ITO conductive glass or a TFT drive circuit;

[0017] S2: mixing the perovskite material, the auxiliary crystallization additive and the precursor solvent to prepare a precursor solution; coating the precursor solution on the electron transport layer; and drying to obtain a highly dense perovskite film;

[0018] S3: coating 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the above-mentioned high-density perovskite film to prepare a hole transport layer;

[0019] S4: Vapor-deposit a layer of gold or silver on the hole transport layer as a metal electrode.

[0020] Preferably, the step S2 is specifically:

[0021] The perovskite material, the auxiliary crystallization additive and the precursor solvent are mixed to prepare a precursor stock solution;

[0022] Coating the precursor solution on the electron transport layer;

[0023] Heat and dry in a vacuum drying oven at 40-180°C for 2-8h;

[0024] In a vacuum evaporation box, the perovskite raw material is used as an evaporation source and evaporated at a temperature of 200-300°C for 0.5-3h to obtain a highly dense perovskite film.

[0025] Preferably, the perovskite material is one or more of FACs2AgBiBr6, FAMACsPbBr3, CsPbBr3, MAPbBr3, Cs2AgBiBr6 and MAPbI3.

[0026] Preferably, the auxiliary crystallization additive is one or more of thiourea, biuret, pyrrole, ammonium chloride, ammonium bromide, ammonium iodide, carbazole, dibenzofuran, imidazoline, butylamine acetate, polyacrylamide, chitosan, cellulose, oleic acid, oleylamine and N,N-diphenylthiourea.

[0027] Preferably, the precursor solvent is one or more of dimethoxyethanol, polyethylene glycol, N-methyl-2-pyrrolidone, N,N-dimethylformamide, chlorobenzene, acetone, dimethyl sulfoxide, dimethylacetamide, chlorobenzene, toluene and chloroform.

[0028] Preferably, the mass ratio of the auxiliary crystallization additive to the perovskite material is (0.001-0.2):1.

[0029] Preferably, the ratio of the auxiliary crystallization additive to the precursor solvent is 0.01 g / ml-0.03 g / ml.

[0030] Preferably, the size of the high-density perovskite film is 2×2 cm 2 -30×30cm 2 .

[0031] Preferably, the coating amount of the precursor solution on the electron transport layer is 0.1-1 g / cm2 of the electron transport layer.

[0032] Preferably, a method for preparing a perovskite X-ray direct detector comprises the following steps:

[0033] S1: Scaling the tin dioxide dispersion onto the ITO conductive glass or TFT driving circuit by scraping, and then transferring to a vacuum drying oven at 70-90°C and drying for 0.5-3h to prepare an electron transport layer;

[0034] S2: adding the perovskite material to the precursor solvent, stirring and dissolving at a temperature of 40-70° C. to obtain a perovskite precursor solution, and then adding an auxiliary crystallization additive to the above solution, stirring and dissolving at a temperature of 40-70° C. to obtain a precursor stock solution;

[0035] Applying a layer of the above-mentioned precursor solution on the electron transport layer by scraping, spraying or spin coating to obtain a perovskite wet film;

[0036] The perovskite wet film is transferred to a vacuum drying oven and heated at 40-180° C. for 2-8 hours to obtain a perovskite film;

[0037] The perovskite film is transferred to a vacuum evaporation box, 5-50 g of the perovskite material is used as an evaporation source, and the perovskite film is evaporated at a temperature of 200-300° C. for 0.5-6 h to obtain a high-density perovskite film;

[0038] S3: A layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene is coated on the above-mentioned high-density perovskite film by scraping to prepare a hole transport layer; the thickness of the hole transport layer is 5-30 nm, preferably 15-25 nm.

[0039] S4: a layer of gold or silver is evaporated on the hole transport layer of step S3 as a metal electrode, with a thickness of 5-500 nm, preferably 10-50 nm.

[0040] Compared with the prior art, the advantages of the present invention are:

[0041] 1) Auxiliary crystallization additives are added to the precursor solution of perovskite, so that the coated perovskite wet film is homogeneously crystallized during the drying process, with smaller grains and higher density, which can effectively fill the pores formed by the evaporation of the solution inside the thick film, further reduce the defects inside the thick film, promote grain boundary fusion, improve charge transfer performance, and reduce dark current. More importantly, during the crystal growth process, it can be integrated with the conductive substrate (ITO glass, TFT drive circuit) to form a compact high-quality perovskite thick film on the conductive substrate, which can be directly used as a device for the assembly and integration of X-ray direct detectors.

[0042] 2) The present invention prepares the perovskite film by a two-step method. In the first step, a high-quality perovskite thick film is prepared by adding an auxiliary crystallization additive to the perovskite stock solution by coating. In the second step, the surface of the perovskite thick film is modified by vacuum evaporation, and a thin perovskite film of the same type is deposited. The surface of the perovskite film prepared by this strategy is smoother, has a higher density, and has better uniformity. In addition, on the basis of the perovskite thick film in the first step, a layer of the same type of perovskite is deposited by atomic deposition. The two are compatible with each other and have good interface contact, which further reduces the defects of the perovskite film and improves the quality of the perovskite film.

[0043] 3) The present invention achieves sufficient absorption of high-energy X-ray photons by constructing a perovskite X-ray absorption film on a conductive substrate with sufficient thickness.

[0044] The invention has reasonable design and simple operation. By integrating the coating on the driving circuit, the thick film is flat and dense, so that large-area devices can be prepared with outstanding effect and mass production can be realized. It can be directly used as the core device of the X-ray direct imaging detector for the assembly and integration of the detector. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a physical picture of a high-quality, large-size thick film of perovskite prepared in Example 1 of the present invention;

[0046] Figure 2 This is a SEM image of a thick film of high-quality and large-sized perovskite prepared in Example 1 of the present invention;

[0047] Figure 3 The X-ray response performance diagram of the high-quality and large-size perovskite thin film X-ray detector prepared in Example 1(a) of the present invention and Comparative Example 1(b);

[0048] Figure 4 This is a SEM image of a thick film of high-quality and large-sized perovskite prepared in Example 2 of the present invention;

[0049] Figure 5 The X-ray response performance diagram of the high-quality and large-size perovskite thin film X-ray detector prepared in Example 2(a) of the present invention and Comparative Example 2(b);

[0050] Figure 6 X-ray response performance diagram of high-quality large-size perovskite thin film X-ray detectors prepared by Example 3(a) of the present invention and Comparative Example 3(b). DETAILED DESCRIPTION

[0051] In order to further highlight the innovation and practical value of the present invention, the present invention will be described in detail below in conjunction with embodiments and drawings. The protection scope of the present invention includes but is not limited to the following embodiments.

[0052] A method for preparing a perovskite X-ray direct detector comprises the following steps:

[0053] S1: Scaling the tin dioxide dispersion onto the ITO conductive glass or TFT driving circuit by scraping, and then transferring to a vacuum drying oven at 70-90°C and drying for 0.5-3h to prepare an electron transport layer;

[0054] Tin dioxide has good electron transport properties and high conductivity, which can effectively improve the transmission efficiency of electrons in devices, reduce the recombination of carriers, and improve the photoelectric performance of devices;

[0055] ITO conductive glass or TFT driving circuit is used as the substrate of the device, providing good conductivity and transparency;

[0056] S2: adding the perovskite material to the precursor solvent, stirring and dissolving at a temperature of 40-70° C. to obtain a perovskite precursor solution, and then adding an auxiliary crystallization additive to the above solution, stirring and dissolving at a temperature of 40-70° C. to obtain a precursor stock solution;

[0057] The perovskite material is one or more of FACs2AgBiBr6, FAMACsPbBr3, CsPbBr3, MAPbBr3, Cs2AgBiBr6 and MAPbI3; as the core absorption material of the X-ray detector, the perovskite material has a high atomic number and excellent photoelectric properties, can directly convert X-ray photons into electrical signals, and realize efficient X-ray detection. Selecting different perovskite materials can adjust the photoelectric properties and stability of the device;

[0058] The auxiliary crystallization additive is one or more of thiourea, biuret, pyrrole, ammonium chloride, ammonium bromide, ammonium iodide, carbazole, dibenzofuran, imidazoline, butylamine acetate, polyacrylamide, chitosan, cellulose, oleic acid, oleylamine and N,N-diphenylthiourea; the nucleation and growth process of perovskite crystals are regulated, and the additive can interact with the perovskite precursor to reduce the nucleation energy barrier, promote uniform nucleation, inhibit excessive grain growth, and reduce the formation of grain boundaries and defects, so as to finally obtain a dense, uniform, high-quality perovskite film;

[0059] The precursor solvent is one or more of dimethoxyethanol, polyethylene glycol, N-methyl-2-pyrrolidone, N,N-dimethylformamide, chlorobenzene, acetone, dimethyl sulfoxide, dimethylacetamide, chlorobenzene, toluene and chloroform; it is used to dissolve the perovskite material and auxiliary crystallization additives to prepare a uniform precursor solution. The choice of solvent affects the viscosity of the solution, the evaporation rate and the growth process of the perovskite crystal, thereby affecting the crystallization quality and morphology of the final film;

[0060] The mass ratio of the auxiliary crystallization additive to the perovskite material is (0.001-0.2): 1;

[0061] The ratio of the auxiliary crystallization additive to the precursor solvent is 0.01 g / ml-0.03 g / ml;

[0062] A layer of the above-mentioned precursor solution is scraped on the electron transport layer by scraping, spraying or spin coating to obtain a perovskite wet film; the coating amount of the precursor solution on the electron transport layer is 0.1-1g / square centimeter of the electron transport layer;

[0063] The perovskite wet film is transferred to a vacuum drying oven and heated at 40-180° C. for 2-8 hours to obtain a perovskite film;

[0064] The perovskite film is transferred to a vacuum evaporation box, 5-50 g of the perovskite material is used as an evaporation source, and the perovskite film is evaporated at a temperature of 200-300° C. for 0.5-6 h to obtain a high-density perovskite film;

[0065] The size of the high-density perovskite film is 2×2 cm 2 -30×30cm 2 ;

[0066] S3: A layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene is coated on the above-mentioned high-density perovskite film by scraping to prepare a hole transport layer; the thickness of the layer is 5-30nm, preferably 15-25nm; 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene is used as a hole transport layer material, which has good hole transport ability and energy level matching, and can effectively transport holes generated in the perovskite layer to the metal electrode, reduce the recombination of carriers, and improve the photoelectric conversion efficiency of the device;

[0067] S4: Evaporate a layer of gold or silver as a metal electrode on the hole transport layer of step S3, with a thickness of 5-500nm, preferably 10-50nm; gold and silver have high conductivity and stability, and have good contact with the hole transport layer to ensure the performance and life of the device.

[0068] Through the organic combination of the above steps and materials, the present invention realizes the preparation of high-density perovskite films, solves the problems of many cracks, many grain boundary defects, thin thickness, rough surface, etc. in traditional perovskite films, and improves the performance of X-ray direct detectors.

[0069] In this specific implementation manner, some raw materials are prepared as follows:

[0070] Preparation method of FAMACsPbBr3: Weigh 587g PbBr2, 64.44g MABr, 6.8g CrBr2, and 200g FABr respectively and dissolve them in 1500mL of a mixed solution of DMF / DMSO (volume ratio 4:1), stir them for 4h to make the solution evenly mixed, then filter it, and then place the filtered solution in an oven at 85°C for 15h for recrystallization to obtain FAMACsPbBr3.

[0071] Preparation method of CsPbBr3: Weigh 36.7g PbBr2 and 21g CrBr2 respectively and dissolve them in 300ml DMF solution, stir them for 3h to make the solution evenly mixed, then filter it, and then place the filtered solution in an oven at 87°C for 18h for recrystallization to obtain CsPbBr3.

[0072] Example 1

[0073] Step S1: Scrape 5 ml of 2 mg / ml tin dioxide dispersion onto a 5×5 cm 2 The TFT driving circuit was then transferred to a vacuum drying oven at 80°C and dried for 1 hour to prepare an electron transport layer;

[0074] Step S2: Dissolve 50 g of the pre-synthesized Cs2AgBiBr3 powder in a mixed solution of 6 ml of dimethyl sulfoxide (DMSO) and 294 mL of chlorobenzene, and stir at 40° C. for 2 h until the powder is completely dissolved to prepare a Cs2AgBiBr3 precursor solution;

[0075] Step S3: Pipette 5 ml of 2 mg / ml thiourea aqueous solution and add it to the Cs2AgBiBr3 precursor solution of step S2, stir for 20 minutes, and after stirring evenly, obtain a precursor stock solution;

[0076] Step S4: coating the precursor solution obtained in step S3 on the electron transport layer in step S1 by blade coating to obtain a Cs2AgBiBr3 wet film; then transferring the obtained Cs2AgBiBr3 wet film to a vacuum oven and drying it at 100° C. for 1 h, thereby obtaining a Cs2AgBiBr3 thick film;

[0077] Step S5: The Cs2AgBiBr3 thick film obtained in step S4 is transferred to a vacuum evaporation box, 20 g of Cs2AgBiBr3 is weighed as an evaporation source, and evaporated at 260° C. for 3 h to obtain a high-density perovskite film with a smooth surface, namely, a Cs2AgBiBr3 perovskite thick film;

[0078] Step S6: coating a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the Cs2AgBiBr3 perovskite thick film obtained in step S5 by blade coating to prepare a hole transport layer with a thickness of 20 nm;

[0079] Step S7: a layer of gold is evaporated on the hole transport layer in step S6 as a metal electrode with a thickness of 30 nm.

[0080] Comparative Example 1

[0081] Step S1: Scrape 5 ml of 2 mg / ml tin dioxide dispersion onto a 5×5 cm 2 The TFT driving circuit was then transferred to a vacuum drying oven at 80°C and dried for 1 h to prepare an electron transport layer.

[0082] Step S2: dissolving 50 g of the pre-synthesized Cs2AgBiBr3 powder in a mixed solution of 6 ml of dimethyl sulfoxide (DMSO) and 294 mL of chlorobenzene, stirring at 40° C. for 2 h until the powder is completely dissolved, to prepare a Cs2AgBiBr3 precursor solution;

[0083] Step S3: coating the precursor solution obtained in step S2 on the electron transport layer in step S2 by blade coating to obtain a Cs2AgBiBr3 wet film; then transferring the obtained wet film to a vacuum oven and drying it at 100° C. for 1 h, thereby obtaining a Cs2AgBiBr3 thick film;

[0084] Step S4: coating a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the Cs2AgBiBr3 perovskite thick film obtained in step S5 by blade coating to prepare a hole transport layer with a thickness of 20 nm;

[0085] Step S5: A layer of gold is evaporated on the hole transport layer in step S4 as a metal electrode with a thickness of 30 nm.

[0086] Figure 1 The embodiment 1 shown in the figure obtains a high-quality, large-size thick film of perovskite, with an area of ​​about 5×5 cm 2 , the film surface is uniform and smooth. Figure 2 This is a SEM cross-sectional view of a high-quality, large-size perovskite thick film of Example 1. From the measurement of the cross-sectional thickness, it can be found that the thickness of the perovskite film we obtained can reach 900um; Figure 3The X-ray response performance diagram of the high-quality large-size perovskite thin film X-ray detector prepared in Example 1(a) of the present invention and Comparative Example 1(b) is shown. Among them, the photocurrent response value of the high-quality large-size perovskite thin film X-ray detector prepared in Example 1(a) is 65.7uGy / s, which is significantly higher than the photocurrent response value of the perovskite thin film X-ray detector prepared in Comparative Example 1 (58.9uGy / s).

[0087] Example 2

[0088] Step S1: Scrape 5 ml of 2 mg / ml tin dioxide dispersion onto a 5×5 cm 2 The TFT driving circuit was then transferred to a vacuum drying oven at 60°C and dried for 2 hours to prepare an electron transport layer;

[0089] Step S2: dissolving 60 g of pre-synthesized CsPbBr3 powder in a mixed solution of 270 ml of N,N-dimethylformamide (DMF) and 30 ml of dimethyl sulfoxide (DMSO) to prepare a perovskite precursor solution, stirring at 60° C. for 2 h until the powder is completely dissolved, to prepare a CsPbBr3 precursor solution;

[0090] Step S3: pipette 5 mg of N,N-diphenylthiourea powder and add it to the CsPbBr3 precursor solution of step S2, stir for 20 minutes, and after stirring evenly, obtain a precursor stock solution;

[0091] Step S4: coating the precursor solution obtained in step S3 on the electron transport layer in step S1 by blade coating to obtain a thick CsPbBr3 wet film; then transferring the obtained wet film to a vacuum oven at 90° C. and drying for 2 h to obtain a CsPbBr3 thick film;

[0092] Step S5: The CsPbBr3 thick film obtained in step S4 is transferred to a vacuum evaporation box, 20 g of CsPbBr3 is weighed as an evaporation source, and evaporated at 300° C. for 2 h to obtain a high-quality CsPbBr3 perovskite thick film with a smooth surface;

[0093] Step S6: coating a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the CsPbBr3 perovskite thick film obtained in step S5 by blade coating to prepare a hole transport layer with a thickness of 20 nm;

[0094] Step S7: a layer of silver is evaporated on the hole transport layer in step S6 as a metal electrode with a thickness of 30 nm.

[0095] Comparative Example 2

[0096] Step S1: Scrape 5 ml of 2 mg / ml tin dioxide dispersion onto a 5×5 cm 2 The TFT driving circuit was then transferred to a vacuum drying oven at 60°C and dried for 2 hours to prepare an electron transport layer;

[0097] Step S2: dissolving 60 g of pre-synthesized CsPbBr3 powder in a mixed solution of 270 ml of N,N-dimethylformamide (DMF) and 30 ml of dimethyl sulfoxide (DMSO) to prepare a perovskite precursor solution, stirring at 60° C. for 2 h until the powder is completely dissolved, to prepare a CsPbBr3 precursor solution;

[0098] Step S3: coating the precursor solution obtained in step S2 on the electron transport layer in step S1 by blade coating to obtain a CsPbBr3 wet film with a thickness of 800 um; then transferring the obtained wet film to a vacuum oven at 90° C. and drying for 2 h, thereby obtaining a CsPbBr3 thick film;

[0099] Step S4: coating a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the CsPbBr3 perovskite thick film obtained in step S3 by blade coating to prepare a hole transport layer with a thickness of 20 nm;

[0100] Step S5: A layer of silver is evaporated on the hole transport layer in step S5 as a metal electrode with a thickness of 30 nm.

[0101] Figure 4 This is a SEM cross-sectional image of a high-quality, large-size perovskite thick film in Example 2. From the measurement of the cross-sectional thickness, it can be found that the thickness of the perovskite film we obtained can reach 800um; Figure 5 The X-ray response performance diagrams of the high-quality large-size perovskite thin film X-ray detectors prepared in Example 2(a) and Comparative Example 2(b) are shown. The photocurrent response value of the high-quality large-size perovskite thin film X-ray detector prepared in Example 2(a) is 125.7uGy / s, which is significantly higher than the photocurrent response value (89uGy / s) of the perovskite thin film X-ray detector prepared in Comparative Example 2.

[0102] Example 3

[0103] Step S1: Scrape 5 ml of 2 mg / ml tin dioxide dispersion onto a 5×5 cm 2 The TFT driving circuit was then transferred to a vacuum drying oven at 60°C and dried for 2 hours to prepare an electron transport layer;

[0104] Step S2: dissolving 70 g of pre-synthesized MAPbI3 powder in 300 ml of N,N-dimethylformamide (DMF) perovskite precursor solution, stirring at 60° C. for 2 h until the powder is completely dissolved, to prepare a MAPbI3 precursor solution;

[0105] Step S3: 10 mg of imidazole was added to the MAPbI3 precursor solution of step S2, and stirred at 60° C. for 1 h until the precursor was completely dissolved to obtain a precursor stock solution;

[0106] Step S4: coating the precursor solution obtained in step S3 on the electron transport layer in step S1 by blade coating to obtain a thick MAPbI3 wet film; then transferring the obtained wet film to a vacuum oven and drying it at 100° C. for 1 hour to obtain a MAPbI3 thick film;

[0107] Step S5: The MAPbI3 thick film obtained in step S4 is transferred to a vacuum evaporation box, 30 g of MAPbI3 is weighed as an evaporation source, and evaporated at 230° C. for 2 h to obtain a high-quality MAPbI3 perovskite thick film with a smooth surface;

[0108] Step S6: coating a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the MAPbI3 perovskite thick film obtained in step S5 by blade coating to prepare a hole transport layer with a thickness of 20 nm;

[0109] Step S7: a layer of silver is evaporated on the hole transport layer in step S6 as a metal electrode with a thickness of 30 nm.

[0110] Comparative Example 3

[0111] Step S1: Scrape 5 ml of 2 mg / ml tin dioxide dispersion onto a 5×5 cm 2 The TFT driving circuit was then transferred to a vacuum drying oven at 60°C and dried for 2 hours to prepare an electron transport layer;

[0112] Step S2: dissolving 1.8 g of pre-synthesized MAPbI3 powder in 100 ml of N,N-dimethylformamide (DMF) perovskite precursor solution, stirring at 60° C. for 2 h until the powder is completely dissolved, to prepare a MAPbI3 precursor solution;

[0113] Step S3: coating the precursor solution obtained in step S3 on the electron transport layer in step S1 by blade coating to obtain a MAPbI3 wet film with a thickness of 1000 um; then transferring the obtained wet film to a vacuum oven and drying it at 100° C. for 1 hour to obtain a MAPbI3 thick film;

[0114] Step S4: coating a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the MAPbI3 perovskite thick film obtained in step S3 by blade coating to prepare a hole transport layer with a thickness of 20 nm;

[0115] Step S5: A layer of silver is evaporated on the hole transport layer in step S4 as a metal electrode with a thickness of 30 nm.

[0116] Figure 6 The X-ray response performance diagram of the high-quality large-size perovskite thin film X-ray detector prepared in Example 3(a) of the present invention and Comparative Example 3(b) is shown. Among them, the photocurrent response value of the high-quality large-size perovskite thin film X-ray detector prepared in Example 3(a) is 47.1uGy / s, which is significantly higher than the photocurrent response value of the perovskite thin film X-ray detector prepared in Comparative Example 3 (35.8uGy / s).

[0117] Embodiment 4:

[0118] Basically the same as Example 2, except that "60 g of CsPbBr3 powder" is adjusted to "60 g of FAMACsPbBr3".

[0119] Embodiment 5:

[0120] Basically the same as Example 2, except that "60 g of CsPbBr3 powder" is adjusted to "30 g of FAMACsPbBr3 and 30 g of CsPbBr3 powder".

[0121] The photocurrent response value of the high-quality large-size perovskite thin film X-ray detector prepared in Example 4 is 145.5 uGy / s, and the photocurrent response value of the high-quality large-size perovskite thin film X-ray detector prepared in Example 5 is 162.0 uGy / s.

[0122] When FAMACsPbBr3 and CsPbBr3 are combined, the two materials work synergistically in terms of crystal structure and energy band structure, significantly improving the photocurrent response value of the perovskite film. + 、MA + , Cs +) can fill the defects in the CsPbBr3 lattice, reduce lattice strain, promote uniform growth of crystals, and reduce the formation of grain boundaries and defects; at the same time, the optimization of energy level matching promotes the effective separation and transmission of photogenerated carriers, and improves the mobility and lifetime of carriers. The synergistic effect of the two improves the density and stability of the film, reduces the dark current, and ultimately achieves synergistic performance. Therefore, preferably, the perovskite material is a mixture of FAMACsPbBr3 and CsPbBr3, and more preferably, the mass ratio of FAMACsPbBr3 and CsPbBr3 is (0.5-2):1.

Claims

1. A method for preparing a high-density perovskite film, characterized in that: The method comprises the following steps: coating a precursor solution on an electron transport layer and then drying the precursor solution, wherein the precursor solution is a precursor solution whose solute is a perovskite material and an auxiliary crystallization additive and whose solvent is a precursor solvent.

2. The method for preparing a high-density perovskite film according to claim 1, characterized in that: The perovskite material is one or more of FACs2AgBiBr6, FAMACsPbBr3, CsPbBr3, MAPbBr3, Cs2AgBiBr6 and MAPbI3.

3. The method for preparing a high-density perovskite film according to claim 1, characterized in that: The auxiliary crystallization additive is one or more of thiourea, biuret, pyrrole, ammonium chloride, ammonium bromide, ammonium iodide, carbazole, dibenzofuran, imidazoline, butylamine acetate, polyacrylamide, chitosan, cellulose, oleic acid, oleylamine and N,N-diphenylthiourea.

4. The method for preparing a high-density perovskite film according to claim 1, characterized in that: The precursor solvent is one or more of dimethoxyethanol, polyethylene glycol, N-methyl-2-pyrrolidone, N,N-dimethylformamide, chlorobenzene, acetone, dimethyl sulfoxide, dimethylacetamide, chlorobenzene, toluene and chloroform.

5. A high-density perovskite film, characterized in that: The method is prepared by any one of claims 1 to 4.

6. Application of the high-density perovskite film as claimed in claim 5 in X-ray detection.

7. The application of the high-density perovskite film in X-ray detection as claimed in claim 6, characterized in that: The high-density perovskite film is used to prepare a perovskite X-ray direct detector.

8. A method for preparing a perovskite X-ray direct detector, comprising the following steps: S1: coating a tin dioxide dispersion on a substrate, drying, and preparing an electron transport layer; the substrate is ITO conductive glass or a TFT drive circuit; S2: mixing the perovskite material, the auxiliary crystallization additive and the precursor solvent to prepare a precursor solution; coating the precursor solution on the electron transport layer; and drying to obtain a highly dense perovskite film; S3: coating 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the above-mentioned high-density perovskite film to prepare a hole transport layer; S4: Vapor-deposit a layer of gold or silver on the hole transport layer as a metal electrode.

9. The method for preparing a perovskite X1-ray direct detector according to claim 8, characterized in that: The step S2 is specifically as follows: The perovskite material, the auxiliary crystallization additive and the precursor solvent are mixed to prepare a precursor stock solution; Coating the precursor solution on the electron transport layer; Heat and dry in a vacuum drying oven at 40-180°C for 2-8h; In a vacuum evaporation box, the perovskite raw material is used as an evaporation source and evaporated at a temperature of 200-300°C for 0.5-3h to obtain a highly dense perovskite film.

10. The method for preparing a perovskite X-ray direct detector according to claim 9, characterized in that: The steps include: S1: Scrape the tin dioxide dispersion onto the ITO conductive glass or TFT drive circuit by scraping, and then transfer to a vacuum drying oven at 70-90°C and dry for 0.5-3h to prepare an electron transport layer; S2: adding the perovskite material to the precursor solvent, stirring and dissolving at a temperature of 40-70° C. to obtain a perovskite precursor solution, and then adding an auxiliary crystallization additive to the above solution, stirring and dissolving at a temperature of 40-70° C. to obtain a precursor stock solution; Applying a layer of the above-mentioned precursor solution on the electron transport layer by scraping, spraying or spin coating to obtain a perovskite wet film; The perovskite wet film is transferred to a vacuum drying oven and heated at 40-180° C. for 2-8 hours to obtain a perovskite film; The perovskite film is transferred to a vacuum evaporation box, 5-50 g of the perovskite material is used as an evaporation source, and the perovskite film is evaporated at a temperature of 200-300° C. for 0.5-6 h to obtain a high-density perovskite film; S3: coating a layer of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene on the high-density perovskite film by blade coating to prepare a hole transport layer; S4: Evaporate a layer of gold or silver on the hole transport layer in step S7 as a metal electrode.

Citation Information

Cited By

  • Methylamino perovskite single crystal, preparation method and X-ray detector thereof

    CN119710934A